New Insights into the Crosstalk between NMDARs and Iron: Implications for Understanding Pathology of Neurological Diseases - Xu, Huamin; Jiang, Hong; Xie, Junxia (Frontiers in Molecular Neuroscience, 2017)
Both iron dyshomeostasis and N-methyl-D-aspartate receptors (NMDARs)-mediated neurotoxicity have been shown to have an important role in neurological diseases such as Parkinson's disease (PD), Alzheimer disease (AD). Evidence proved that activation of NMDARs could promote iron overload and iron-induced neurotoxicity by enhancing iron importer divalent metal transporter 1 (DMT1)-mediated iron uptake and iron releasing from lysosome. Also, iron overload could regulate NMDARs-mediated synaptic transmission. This indicates that there might be a possible relationship between iron and activation of NMDARs in neurological diseases. Understanding this interaction between iron and activation of NMDARs may provide new therapeutic avenues for a more targeted neurotherapeutic strategy for these diseases. Therefore, in this review, we will summarize the new insight into the mechanisms underlying the interaction between iron and activation of NMDARs, and describe the roles of iron and NMDARs activation in pathogenesis of neurological diseases including PD and AD.